Proximal caries lesion detection in primary teeth: does this justify the association of diagnostic methods? - Bussaneli, D. G. [UNESP]; Restrepo, M.; Boldieri, T.; Albertoni, T. H.; Santos-Pinto, L.; Cordeiro, R. C. L. (Springer, 2015)
The aim of this clinical study was to evaluate and compare the performance of visual exam with use of the Nyvad criteria (visual examination - (VE)), interproximal radiography (BW), laser fluorescence device (DIAGNOdent Pen-DDPen), and their association in the diagnosis of proximal lesions in primary teeth. For this purpose, 45 children (n = 59 surfaces) of both sexes, aged between 5 and 9 years were selected, who presented healthy primary molars or primary molars with signs suggestive of the presence of caries lesions. The surfaces were clinically evaluated and coded according to the Nyvad criteria and immediately afterwards with the DDPen. Radiographic exam was performed only on the surfaces coded with Nyvad scores 2, 3, 5, or 6. Active caries lesions and/or those with discontinuous surfaces were restored, considering the depth of lesion as reference standard. Sensitivity, specificity, accuracy, and area under ROC curve were calculated for each technique and its associations. Visual exam with Nyvad criteria presented the highest specificity, accuracy, and area under ROC curve values. The DDPen presented the highest sensitivity values. Association with one or more methods resulted in an increase in specificity. The performance of visual, radiographic, and DDpen exams and their associations were good; however, the clinical examination with the Nyvad criteria was sufficient for the diagnosis of interproximal lesions in primary teeth.
Keywords: Dental caries; Fluorescence; Dental radiography; Lasers; Diagnosis